Designing Snake and Ladder Game as an Instructional Media to Teach English Vocabulary - Pratama, Novelia; Mahbub, Moh. Arif; Al Fauzi, Fatih (Linguapedia, 2022)
This study is categorized as Educational Research and Development (RnD). The employment was purposed to embody the appropriate instructional media to teach English vocabulary for Intermediate students’ level of Yoko‟s English course, Ambulu. The research product named Gumiho snake and Ladder game. That was designed based on the competence of Yoko‟s English Course, the finding data gathered through need analysis and Contextual Teaching Learning (CTL). Concerning to these, a set of procedures proposed by Borg and Gall are being applied in this study. The research instruments used to collect the data consisted of Course, Focused Group Discussion (FGD), interview, questionnaires, observation sheet and checklist validation forms. Expert validation was carried out to evaluate the game developed for the product betterment. Moreover, to know the applicability of the materials and students‟ responses, the real try-out phase on some selected chapters during the research period had been conducted. For the reasons, the Snake and Ladder game as a instructional media for Yoko’s program students is ready to be applied in teaching learning activity.